A multilevel analysis of collective efficacy, neighborhood disorder, and individual social capital on avoidance behavior - Hardyns, Wim (Crime & delinquency, 2019)
The principal aim of this multilevel study was to assess the impact of collective efficacy and disorder, as neighborhood characteristics, and individual social capital on an individual’s avoidance behavior, independent of the neighborhood composition. The theoretical backdrop to the present study integrates insights from social capital theory, collective efficacy theory, and broken windows theory. The multilevel model is based on an individual-level questionnaire of inhabitants (N = 2,730) and a neighborhood-level questionnaire of key informants in neighborhoods in Ghent, Belgium (N = 142). The results suggest small but significant neighborhood effects on an individual’s avoidance behavior. Individuals with lower levels of individual social capital and who live in neighborhoods with higher levels of disorder report more avoidance behavior.